Dynamic 4D-CT Angiography post-EVAR for Early Detection, Classification, and Management of Endoleaks - Panayiotou, Natalie (My University, 2024)
Abdominal aortic aneurysms are defined as an abnormal, irreversible dilatation of the abdominal aorta typically exceeding 3 cm in the greatest diameter or more than 50% of its normal anteroposterior diameter. The primary minimal intervention treatment of abdominal aortic aneurysms are endovascular aneurysm repairs. Endoleak is considered the most commonly occurring complication after EVAR, thus demanding frequent post operative follow-ups.Endoleaks represent persistent perfusion into the residual aneurysm sac, that may lead in sac expansion. Therefore, accurate diagnosis of endoleak type using adequate imaging surveillance or re-intervention is crucial for better long-term survival rates. The main aim of this study is to evaluate an innovative customized dynamic CTA imaging protocol for the early detection, classification, and management of endoleaks following endovascular aneurysm repair of abdominal aortic aneurysms. The establishment of this protocol improves the accuracy and confidence in detecting or excluding the presence of endoleaks. Triphasic conventional computed tomography angiography protocol, routinely performed for endovascular aneurysm repair surveillance involves three static images of unenhanced, arterial and delayed venous phase. However, the variability in contrast arrival and washout time and the complexity of the stent graft for each patient in CT imaging precludes accurate characterization of endoleak type and identifying target vessels for the treatment of safe and targeted re-intervention. In recent years, advanced dual-source dual-energy CT systems with alternating table positions allow for dynamic acquisitions of the endograft's hemodynamics, the aneurysm sac, and all the aortic branches with a continuous visualization of the contrast media flow, thus detecting with accuracy the type of endoleak. Ten patients scheduled for their routine CTA examination of the abdominal aorta post EVAR at German Oncology Center, were prospectively studied. Two patients were excluded from the study because of the absence of endoleaks. This retrospective study was approved by the local Bioethics committee (2023.01.166) and all participants provided written informed consent before the examination. vii The patients were examined with a time-resolved CT angiographic protocol consisting of 12 low-dose phases with 60-80 mL of iodine contrast media. A dual energy acquisition was obtained as a delayed scan having the valuable benefits of the two x-ray photon energy spectra. Even when the venous phase was acquired too late or too early and contrast washed out, the application of virtual monoenergetic images and iodine maps increased the visualization of contrast enhancement. The dynamic series were assessed with the use of syngo. CT Dynamic Angio and syngo. CT Body Perfusion application in order to analyze them quantitatively and qualitatively and provide quantitative parameters to maximize the accuracy of the endoleak source. The venous dual energy series were assessed with the use of syngo. CT Dual Energy application to identify any minimal, low flow endoleaks. The dCTA revealed eight type II endoleaks and one type I endoleak. The analysis, conducted using dynamic CT angiography, revealed a significant difference in the mean enhancement between the aorta and endoleak. Certain endoleaks have a slow flow, appearing between 40 to 44 seconds after contrast injection, while others manifest as early leaks, detected between 24 to 37 seconds. The phase with the best contrast enhancement among the 12 phases of our time-resolved CTA protocol showed a mean attenuation value in the aortic lumen for all the patients 737.8 HU. The mean attenuation value of the aneurysm sac (noise) was 47 HU. Mean attenuation value of the endoleak was 555 HU. The average contrast-to-noise ratio of the aortic lumen for all the dynamic CTA phases was 16 and the average CNR of the endoleak was 11.8. All patients did not have a significant change in their aneurysm sac diameter except patients 6 and 10 who had a 19.6% increment of the aneurysm diameter and 12.9% respectively. Also, the same patients had a significant SVG with both the manual volumetric measurement method of the aneurysm sac and the ellipsoid method. The mean protocol radiation dose was 1134 mGy cm and the mean effective dose was 17.0 mSv. The overall average score of the quality assessment, encompassing evaluations from all the radiologists, was reported as 4 categorizing the protocol as ‘good’. The systematic review of the published studies designates that, the DLP of the dynamic CTA protocol, which includes a noncontrast phase, a dynamic phase with 12 series, and a dual-energy venous phase, is in most cases significantly lower than the conventional CTA protocol. Additionally, the contrast media volume being given to the patients with dynamic CTA protocols was significantly lower than the contrast media volume of the viii cCTA protocol due to the lowest tube kV used in the dynamic CTA protocol. This ustocustomized dynamic CT protocol had a lower contrast dose compared to other publications and a lower/comparable radiation dose. The thesis concludes that 4D CTΑ with the use of quantitative analysis regarding perfusion maps showed excellent diagnostic accuracy and demonstrated feasibility in objective endoleak analysis and can aid the differential diagnosis of endoleak types. This study introduces a novelty protocol that combines dynamic CTA and dual energy for evaluating the presence of endoleaks. Furthermore, no other study or publication has employed both the ellipsoid and volumetric methods to measure sac volume growth and subsequently compared these values. Additionally, no other assessment of endoleak revealed endoleak iodine concentration values extracted from the dual energy iodine maps. Some future perspectives for this thesis involve expanding the patient sample size to enable a more comprehensive evaluation of the protocol across a larger population and explore additional perfusion parameters to ascertain whether the endoleak represents a high or low-risk leakage based on these perfusion values. Also, iodine concentrations can provide a potential biomarker for diagnosis of a sac enlargement or a high/low flow endoleaks.
Keywords: dynamic computed tomography angiography; EVAR; endoleak; dual energy; perfusion